Age‐related decline in murine heart and skeletal muscle performance is attenuated by reduced Ahnak1 expression. Issue 5 (1st July 2021) - Mahmoodzadeh, Shokoufeh; Koch, Katharina; Schriever, Cindy; Xu, Jingman; Steinecker, Maria; Leber, Joachim; Dworatzek, Elke; Purfürst, Bettina; Kunz, Severine; Recchia, Deborah; Canepari, Monica; Heuser, Arnd; et al.
Abstract: Background: Aging is associated with a progressive reduction in cellular function leading to poor health and loss of physical performance. Mitochondrial dysfunction is one of the hallmarks of aging; hence, interventions targeting mitochondrial dysfunction have the potential to provide preventive and therapeutic benefits to elderly individuals. Meta‐analyses of age‐related gene expression profiles showed that the expression of Ahnak1, a protein regulating several signal‐transduction pathways including metabolic homeostasis, is increased with age, which is associated with low VO2MAX and poor muscle fitness. However, the role of Ahnak1 in the aging process remained unknown. Here, we investigated the age‐related role of Ahnak1 in murine exercise capacity, mitochondrial function, and contractile function of cardiac and skeletal muscles. Methods: We employed 15‐ to 16‐month‐old female and male Ahnak1‐knockout (Ahnak1‐KO) and wild‐type (WT) mice and performed morphometric, biochemical, and bioenergetics assays to evaluate the effects of Ahnak1 on exercise capacity and mitochondrial morphology and function in cardiomyocytes and tibialis anterior (TA) muscle. A human left ventricular (LV) cardiomyocyte cell line (AC16) was used to investigate the direct role of Ahnak1 in cardiomyocytes. Results: We found that the level of Ahnak1 protein is significantly up‐regulated with age in the murine LV (1.9‐fold) and TA (1.8‐fold) tissues. The suppression of Ahnak1 was associated with improved exercise tolerance, as all aged adult Ahnak1‐KO mice (100%) successfully completed the running programme, whereas approximately 31% male and 8% female WT mice could maintain the required running speed and distance. Transmission electron microscopic studies showed that LV and TA tissue specimens of aged adult Ahnak1‐KO of both sexes have significantly more enlarged/elongated mitochondria and less small mitochondria compared with WT littermates ( P < 0.01 and P < 0.001, respectively) at basal level. Further, we observed a shift in mitochondrial fission/fusion balance towards fusion in cardiomyocytes and TA muscle from aged adult Ahnak1‐KO mice. The maximal and reserve respiratory capacities were significantly higher in cardiomyocytes from aged adult Ahnak1‐KO mice compared with the WT counterparts ( P < 0.05 and P < 0.01, respectively). Cardiomyocyte contractility and fatigue resistance of TA muscles were significantly increased in Ahnak1‐KO mice of both sexes, compared with the WT groups. In vitro studies using AC16 cells have confirmed that the alteration of mitochondrial function is indeed a direct effect of Ahnak1. Finally, we presented Ahnak1 as a novel cardiac mitochondrial membrane‐associated protein. Conclusions: Our data suggest that Ahnak1 is involved in age‐related cardiac and skeletal muscle dysfunction and could therefore serve as a promising therapeutical target.